The Process of Group Consultant Providing according to Psychology : The Testing Group’s Temper - Payññāwūḍḍho, Phrakhrubhavanaveeranusith; Buddhadhammo, PhraKrupipithpariyattikit; Srivijitravorakul, Sompoch (วารสารสันติศึกษาปริทรรศน์ มจร, 2016)
It is a well-known fact that psychology is a branch of science concerning mental phenomena, behaviour and process. In this regard, the process of testing group’s temper is said to have become a unique way of consultancy for many practitioners of Dhamma. While utilizing the mentioned technique, a meditation teacher is required for guiding and testing temper; he should act as a good friend so that the perfect practice of Dhamma based on the right and happy way can be achieved. Based on researcher’s direct experiences concerning testing group’s temper, actually, it appeared that the regular consultancy given and observed by past groups of meditation teacher to single practitioner becomes rather suitable technique than a group’s one. But, the researcher as a meditation teacher is interested in psychological testing group’s temper so as to provide a way for further study and improvement. In this article, the following issues are discussed: the ideas and theories of western and eastern consultant psychology, the process of group consultant providing according to psychology, the psychological principle of group consultancy, the psychological following-up on group consultancy, the test of group’s temper, the original order and benefit of testing group’s temper. These would pave the way for further study.